Changes in 24 h Rhythmicity of Spontaneous Locomotor Activity in the Triple Transgenic Mouse for Alzheimer's Disease (3xTg-AD) in a Jet Lag Protocol: Correlations with Retinal Sensitivity. Issue 1 (27th May 2021) - González-Luna, Irma Angélica; Juárez-Tapia, Cinthia; Aguilar-Vázquez, Azucena; Arnold, Edith; Díaz-Cintra, Sofia; Miranda-Anaya, Manuel; Díaz-Muñoz, Mauricio
The progression of amyloid plaques and neurofibrillary tangles in different brain areas is associated with the effects of Alzheimer's disease (AD). In addition to cognitive impairment, circadian alterations in locomotor activity have also been detected, but they have not been characterized in a jet lag protocol. Therefore, the present study aimed to compare 3xTg-AD and non-transgenic mice in changes of 24 h cycles of spontaneous locomotor activity in a jet lag protocol, in an environment without a running wheel, at 3 different states of neuronal damage: early, intermediate and advanced (3, 8 and 13 months, respectively). The 3xTg-AD mice at 3 months presented differences in phase angle and acrophase, and differentially increased activity after advances more than after delays. At 13 months, a shortening of the free-running period in constant darkness was also noted. 3xTg-AD mice showed a significant increase (123%) in global activity at 8 to 13 months and in nighttime activity (153%) at 13 months. In the advance protocol (ADV), 3xTg-AD mice displayed a significant increase in global activity (171%) at 8 and 13 months. The differences in masking effect were evident at 8 months. To assess a possible retinal dysfunction that could interfere with photic entrainment as part of the neurodegenerative process, we compared electroretinogram recordings. The results showed early deterioration in the retinal response to light flashes in mesopic conditions, observed in the B-wave latency and amplitude. Thus, our study presents new behavioral and pathological characteristics of 3xTg-AD mice and reveals the usefulness of non-invasive tools in early diagnosis.